Benefits and Safety of Astaxanthin in the Treatment of Mild-To-Moderate Dry Eye Disease - Tian, Lei; Wen, Ya; Li, Siyuan; Zhang, Peng; Wang, Yinghui; Wang, Jingyi; Cao, Kai; Du, Lihua; Wang, Ningli; Jie, Ying (Frontiers in Nutrition, 2022)
Abstract: Objectives: To evaluate the effect of astaxanthin in the treatment of mild-to-moderate dry eye disease (DED) in middle-aged and elderly patients. Methods: 120 eyes of 60 middle-aged and elderly patients with mild-to-moderate DED were enrolled in this prospective, one-group, quasi-experimental study. 6mg Astaxanthin tablets (Weihong Haematococcus Pluvialis Astaxanthin, Hangzhou Xinwei Low Carbon Technology R&D Co., Ltd., China) were administered orally, twice daily for 30±2 days. History of eye diseases, treatment, systemic disease, and medication before the test were recorded. In addition, the ocular surface disease index (OSDI) questionnaire, noninvasive tear break-up time (NIBUT), fluorescein break-up time (FBUT), corneal fluorescein staining (CFS) score, eyelid margin signs, meibomian gland (MG) expressibility, meibum quality, meibomian gland dropout (MGDR), Schirmer I test (SIt), tear meniscus height (TMH), bulbar conjunctiva congestion degree, blink frequency, incomplete blink rate, and thickness of tear film lipid layer were collected before treatment, 2 weeks after the initiation of treatment, and at the end of treatment. Visual acuity (VA), intraocular pressure (IOP), anterior segment, fundus, discomfort symptoms and other adverse reactions were also monitored throughout the study to assess the safety. Results: OSDI score, NIBUT, BUT, CFS score, eyelid margin signs, MG expressibility, meibum quality, and blink frequency improved significantly to varying degrees after treatment compared with those before the treatment (P<0.05), while TMH, SIt, conjunctival congestion, the thickness of tear film lipid layer, MGDR, incomplete blink rate, VA and IOP did not differ (P>0.05). Conclusions: Oral administration of astaxanthin improves the symptoms and signs of middle-aged and elderly patients with mild-to-moderate DED. Clinical Trial Registration No. ChiCTR2100044243.